The possibility of Nalbuphin CoO(OH)-assisted electrochemical detection and its mathematical description - Романів, Людмила Вікторівна (Albanian Journal of Pharmaceutical Sciences, 2016)
The possibility of nalbuphin electrochemical determination over a CoO(OH)-modified electrode has been studied from the theoretical point of view. The correspondent mathematical model has been developed and analyzed by means of linear stability theory and bifurcation analysis. It was shown that CoO(OH) may be applied as an efficient electrode modifier in the detection of nalbuphin in neutral and lightly alkaline media. The electrochemical response has to be clear and easy to interpret. The possibility of the oscillatory and monotonic instabilities has also been verified.
Keywords: nalbuphin, chemically modified electrodes, cobalt (III) oxyhydroxide, electrochemical detection, stable steady-state